Atmospheric pCO2 Response to Stimulated Organic Carbon Export: Sensitivity Patterns and Timescales - Mark Holzer; Tim DeVries; Benoît Pasquier (Geophysical Research Letters)
Abstract The ocean's organic carbon export is a key control on atmospheric pCO2 and stimulating this export could potentially mitigate climate change. We use a data‐constrained model to calculate the sensitivity of atmospheric pCO2 to local changes in export using an adjoint approach. A perpetual enhancement of the biological pump's export by 0.1 PgC/yr could achieve a roughly 1% reduction in pCO2 at average sensitivity. The sensitivity varies roughly 5‐fold across different ocean regions and is proportional to the difference between the mean sequestration time τseq of regenerated carbon and the response time τpre of performed carbon, which is the reduction in the preformed carbon inventory per unit increase in local export production. Air‐sea CO2 disequilibrium modulates the geographic pattern of τpre, causing particularly high sensitivities (2–3 times the global mean) in the Antarctic Divergence region of the Southern Ocean.